-2t+7=5t

Simple and best practice solution for -2t+7=5t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2t+7=5t equation:


Simplifying
-2t + 7 = 5t

Reorder the terms:
7 + -2t = 5t

Solving
7 + -2t = 5t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-5t' to each side of the equation.
7 + -2t + -5t = 5t + -5t

Combine like terms: -2t + -5t = -7t
7 + -7t = 5t + -5t

Combine like terms: 5t + -5t = 0
7 + -7t = 0

Add '-7' to each side of the equation.
7 + -7 + -7t = 0 + -7

Combine like terms: 7 + -7 = 0
0 + -7t = 0 + -7
-7t = 0 + -7

Combine like terms: 0 + -7 = -7
-7t = -7

Divide each side by '-7'.
t = 1

Simplifying
t = 1

See similar equations:

| -3f=-f-10 | | x-8=-2x+3 | | -10u=-9-9u | | -4(x-3)-3x=2(6-3x)-3x | | -6+14+4=32 | | W+(w+2)=-27 | | 10+6z=5z | | 9p-10=10p | | 9-(5a+2)=-a+5 | | 8x^2-6x^2+7x=0 | | -6-3b=-4b | | 4cos^2x=5sinx-2 | | 9-4(4x-3)=3 | | 7x+5x=0 | | 4x^2+8x^2=0 | | 13+d-27=-3 | | 6(3x+6)=-3x-5(1+4x) | | 7/2=1/9x+26/9 | | 4x^2+3x^2-2x=0 | | 2=X+3x^2 | | -3(7n+4)=-2n+26 | | F(19)=4x+7 | | 256=(-4)x | | 0=-10k+5k | | x=-2+8 | | 5x+2(x+4)=5(2x+10) | | 3(-6-7b)=4(-5b-6) | | 11x+53=7x+55 | | -3-c-6=-3c-6 | | 0.02x-1=2.50 | | x+-10=2y | | -4(2x-3)=-4+6(x-4) |

Equations solver categories